What is the role of race in educational psychology? A review of research in Educational Psychologist. Issue 1 (2nd January 2023) - Kumar, Revathy; DeCuir-Gunby, Jessica
Abstract: Acknowledging that educational psychologists should be deliberate in integrating race-related issues in their research, we aim to examine the extent to which articles published in Educational Psychologist issues to date have done so. Based on an iterative search using Boolean/phrase search terms minority, ethnicity, race, culture, equity, justice, racial and ethnic, thirty-one articles (3.2% of all articles published from 1963 to 2022) met the selection criteria, with twelve of these appearing in special issues devoted specifically to race and ethnicity. Review and analyses demonstrated that the articles addressed four major themes, namely: evolving conceptualization of race, ethnicity, and culture; psychological processes; cultural, contextual, and structural factors; and methodology. From 1990 to 2022 there was and is a growing awareness for greater conceptual clarity in defining race and race-related constructs. During this time period, articles reviewed suggest a growing realization of the need to take a more situated perspective and to utilize a broader repertoire of research methods in educational psychology research. No specific trends were observed across articles in the psychological issues discussed in Educational Psychologist . We conclude with recommendations for enabling the journal and the field to become more race-focused for promoting anti-racist education.